3XL News: A Cross-lingual News Aggregator and Reader - Belyaeva, Evgenia; Berčič, Jan; Bercic, Katja; Fuart, Flavio; Košmerlj, Aljaž; Muhič, Andrej; Rehar, Aljoša; Rupnik, Jan; Trampuš, Mitja (SPRINGER INT PUBLISHING AG, GEWERBESTRASSE 11, CHAM, CH-6330, SWITZERLAND, 2015)
We present 3XL News, a multi-lingual news aggregation application for iPad that provides real-time, comprehensive, global and multilingual news coverage. Using methods, developed within the XLike project, for semantic data extraction from news articles and linking of news stories we are able to construct a concise, yet in-depth view of current news stories and their semantic relation. This enables users real-time monitoring of current global events and analysis of diverse reporting in different languages and navigation across related news stories.